1998
DOI: 10.1111/j.1553-2712.1998.tb02504.x
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Risk Factors in Emergency Department Patients: A Multisite Survey

Abstract: Abstract. Background: Many people rely on EDs for routine health care. Often, however, screening and counseling for health risks are not provided. Objective: To determine prevalence rates of chronic disease and injury risk factors and access to routine health care in a random sample of ED patients in 3 cities. Methods: A prospective survey was conducted a t 3 hospital EDs in Akron, OH, Boston, MA, and Denver, CO. A modified version of the national Behavioral Risk Factor Surveillance Survey was administered by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
3

Year Published

2001
2001
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(69 citation statements)
references
References 16 publications
2
64
3
Order By: Relevance
“…5 ED patients are 1.5-3.0 times more likely to reportheavydrinkingorconsequencesthanthose in primary care. 6 Among ED patients, 31% screen positive on the CAGE instrument (≥ 2 questions), 7 more than 10% of patients meet DSMIVorICD-10criteriaforalcoholdependence, 8 and 25% are positive on the Alcohol Use Disorders Identification Test (AUDIT) using a probability sample. 9 In a five year follow-up, alcohol intoxicated ED patients had twice the mortality rate as the non-intoxicated comparison group.…”
Section: Introduction the Rationale For Emergency Department (Ed) Scrmentioning
confidence: 99%
“…5 ED patients are 1.5-3.0 times more likely to reportheavydrinkingorconsequencesthanthose in primary care. 6 Among ED patients, 31% screen positive on the CAGE instrument (≥ 2 questions), 7 more than 10% of patients meet DSMIVorICD-10criteriaforalcoholdependence, 8 and 25% are positive on the Alcohol Use Disorders Identification Test (AUDIT) using a probability sample. 9 In a five year follow-up, alcohol intoxicated ED patients had twice the mortality rate as the non-intoxicated comparison group.…”
Section: Introduction the Rationale For Emergency Department (Ed) Scrmentioning
confidence: 99%
“…Furthermore, researchers have found that ED populations are "high injury risk" groups, and those individuals that utilize emergency care services are at greater risk for injury and repeat ED visits for trauma. 2,3 Moreover, epidemiologic studies show that children of certain minority groups are at higher risk of dying in motor vehicle crashes. 4 Despite the large number of resources allocated to media campaigns, infants and young children continue to travel unrestrained, in unsafe seating positions, and in front passenger seats of airbagequipped vehicles.…”
mentioning
confidence: 99%
“…In a multisite survey, 8 Lowenstein et al reported that in addition to multiple other health risks, 23% of ED patients were at-risk drinkers (positive CAGE screen), 53% did not regularly use seat belts, and 48% smoked cigarettes. Many of them lacked the basic screening and preventive services for early detection and prevention of chronic disease.…”
Section: Do Our Patients Get What They Need?mentioning
confidence: 99%